PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING BERBASIS KEARIFAN LOKAL TERHADAP KEMAMPUAN BAHASA EKSPRESIF ANAK USIA 5-6 TAHUN DI RA PERWANIDA 3 SALEPPA - Reski Rahayu; Herman Herman; Sri Wahyuni Astuti (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah UI BBC, 2024)
This study aims to determine the influence of project based learning model based on local wisdom on the expressive language ability of 5-6 year old children at RA Perwanida 3 Saleppa. The research approach used in this study is a quantitative approach with the Nonequivalent Control Group Design research design. The population in this study consisted of 46 students at RA Perwanida 3 Saleppa. Sampling in this study was purposive sampling. The sample in this study was 20 children with 10 children as the experimental group and 10 children as the control group. The data collection technique used was descriptive statistical analysis and non-parametric statistical analysis. The results of the data analysis obtained Asym (2-tailed) = 0.005 <0.05 accepted and Ho rejected meaning that the expressive language ability in the experimental class is better than the control class, this proves that the project based learning model based on local wisdom has a significant influence on the expressive language ability of children.